Estudo do conflito agrario pela posse das terras tradicionais dos povos indígenas Guarani-Kaiowá no Mato Grosso do Sul - Silva, Yasmine Altimare da (2017)
The dissertation deals with the dispute over the traditional territory of the Panambi Guyraroka and Guyra Kambi'y lndigenous Lands of the Guarani-Kaiowá Indigenous Lands located in the State of Mato Grosso do Sul. For this purpose, we examine the Judiciary's actions in these judicial conflicts, in which the Guarani-Kaiowá indigenous communities are parties and litigants for the possession of their lands. The investigation examines the concept and interpretation of indigenous ownership by theorists, magistrates, judges, and ministers, based on the collective possessory rights of indigenous peoples that are constitutionally foreseen and protected by the Federal Constitution of 1988, article 231. The first chapter discusses the history of the territorial occupation of the state of Mato Grosso do Sul, which resulted in the forced displacement of the Indians implying the current distribution of the Indigenous Lands. lt is also in this chapter that the research problem is drawn, based on the choice of the case study, through the investigation of indicators indicated by the National Indian Foundation, annual reports of the Pastoral Land Commission and the Indian Missionary Council. The second chapter establishes the link between agrarian and indigenous rights, conceptualizing and counteracting them; as well as assesses the concepts of civilian land tenure and ethnic ownership. The third chapter discusses the path of recognition for the right and protection of the lands of the Guarani-Kaiowá communities. From the diagnosis of these processes, there is an evaluation of the positions and judgments of the superior courts and precedents that influenced these decisions, bringing as a reflection the jurisprudential creation called Temporal Framework, used as theoretical support for annulment of the demarcation process of the Guarani-Kaiowá Indigenous Lands.